2020
DOI: 10.1017/s0959270920000222
|View full text |Cite
|
Sign up to set email alerts
|

Conservation status of the recently described Ecuadorian Amazon parrot Amazona lilacina

Abstract: Summary Amazona lilacina is a threatened species endemic to Ecuador, existing across a patchwork of mangroves, lowland coastal forests, agricultural and community owned land. The species was described in 2014 and listed as ‘Endangered’ on the IUCN Red List, however, full assessment of the population was lacking. Using a combination of field observations, roost surveys and community questionnaires, conducted over the last 20 years, we provide up-to-date information on the species’ Extent of Occurrence, estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…We also found that capture location corresponded to the occupation of the poacher, which may explain the variation between rural communities as occupation depends heavily on location, i.e., in-land or coastal. Our trapping pressure index identified that the southern distribution of the species is likely to be at greatest risk, which agrees with earlier work showing a vast population decline in this area [17] and provides further evidence that this area should be prioritised for conservation support.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We also found that capture location corresponded to the occupation of the poacher, which may explain the variation between rural communities as occupation depends heavily on location, i.e., in-land or coastal. Our trapping pressure index identified that the southern distribution of the species is likely to be at greatest risk, which agrees with earlier work showing a vast population decline in this area [17] and provides further evidence that this area should be prioritised for conservation support.…”
Section: Discussionsupporting
confidence: 90%
“…These communities ranged in size from 50 to 300 people. The reason these sites were chosen was because our focus was on understanding risk to Lilacine Amazons, so the selected communities fell within the species extent of occurrence and were <15 km away from key roosting, nesting and feeding grounds [17]. These 12 communities were grouped into four clusters ( Figure 1).…”
Section: Interviews To Quantify Parrot Ownership Trapping and Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although international bans have largely reduced the legal trade on parrots [42,49] and the upsurge of captive-breeding [6,49] has reduced the demand of wild-caught traded birds, illegal trade is still active [50], although at much lower volumes, including illegal trade on African grey parrots [51]. Nonetheless, while international trade is a matter of concern, less attention has been paid to the conservation impact of domestic trade on parrots, even though it is known to occur in different regions of the world, such as Madagascar [52], Asia [34], and all across the Neotropical region [9,23,35,38,39,[53][54][55][56][57]. Due to its illegal nature, the true scale and impact of parrot poaching are often underestimated [34] and based mainly on counts from pet markets [53,55,58], government seizures, or other information sources difficult to verify [9,35,53].…”
Section: Conservation Implications Of Selective Parrot Poachingmentioning
confidence: 99%